Design And Simulation Of 10 kW BLDC Motor Speed Control For Electric Vehicles Using FOC Based On Fuzzy Logic Control - Rizqulloh, Mochamad Shofwan; Pamuji, Feby Agung; Suryoatmojo, Heri (JAREE (Journal on Advanced Research in Electrical Engineering), 2024)
The use of electric vehicles in the current era has begun to spread evenly. Apart from the issue of air pollution produced by ICE vehicles, the ease and practicality of using electric vehicles is the reason why the public is starting to become interested in electric vehicles. Electric vehicle manufacturers are currently choosing BLDC motors for their production vehicles because they are considered suitable for applications that require high power and torque output. However, BLDC motors require more complicated control techniques than other DC motors. The commonly used BLDC motor speed control methods are trapezoidal scalar control and field oriented control. FOC is a type of BLDC motor control with a vector control method which has advantages in terms of efficiency compared to scalar control methods. Many studies on implementing FOC as speed control for BLDC motors, but the research that has been carried out still uses PI control as a basis, where it is known that PI control has shortcomings in the form of complexity in its design. Fuzzy Logic Control is known to be easy to design and reliable in control, so this paper will show the performance of Fuzzy-PI based FOC control as speed control for 10kW BLDC motor in simulation using Simulink program. The simulation results of proposed Fuzzy-PI based FOC method have better response than PI based FOC in terms of starting response with 6.43 times faster rise time, 2.45 times faster settling time, 96.31% lower overshoot value and reliability in overcoming disturbances up to 78.05% lower overshoot value and 2.33 times faster recovery time.